The SMOOTH-Robot: A Modular, Interactive Service Robot - Krüger, Norbert; Fischer, Kerstin; Manoonpong, Poramate; Palinko, Oskar; Bodenhagen, Leon; Baumann, Timo; Kjærum, Jens; Rano, Ignacio; Naik, Lakshadeep; Juel, William Kristian; Haarslev, Frederik; Ignasov, Jevgeni; et al. (Frontiers in Robotics and AI, 2021)
The SMOOTH-robot is a mobile robot that—due to its modularity—combines a relatively low price with the possibility to be used for a large variety of tasks in a wide range of domains. In this article, we demonstrate the potential of the SMOOTH-robot through three use cases, two of which were performed in elderly care homes. The robot is designed so that it can either make itself ready or be quickly changed by staff to perform different tasks. We carefully considered important design parameters such as the appearance, intended and unintended interactions with users, and the technical complexity, in order to achieve high acceptability and a sufficient degree of utilization of the robot. Three demonstrated use cases indicate that such a robot could contribute to an improved work environment, having the potential to free resources of care staff which could be allocated to actual care-giving tasks. Moreover, the SMOOTH-robot can be used in many other domains, as we will also exemplify in this article.